Health and lifestyle in the Iron Age Italian community of Pontecagnano (Campania, Italy, 7th-6th century BCE) - Roberto Germano; Owen Alexander Higgins; Emanuela Cristiani; Alessia Galbusera; Carmen Esposito; Dulce Neves; Carmine Pellegrino; Alessandra Sperduti; Giorgio Manzi; Luca Bondioli; Alessia Nava (PLoS ONE, 2026)
This study investigates health, dental development, diet, and human-environment interactions in individuals buried in the necropolises of Pontecagnano (Campania, Italy, 7th-6th century BCE), using an integrated approach merging dental histomorphometry and calculus micro-residue analysis. The sample consists of 30 permanent teeth (canines, first and second molars) from 10 individuals. Histomorphometric analysis of dental thin sections allowed the estimation of crown formation times, initial cusp formation, crown completion, and enamel extension rates. The prevalence of Accentuated Lines, marking physiological stress events, was analyzed chronologically across tooth classes. Dental calculus analysis was performed on five individuals, identifying plant micro-remains and fungal spores. Crown formation times varied by tooth class, with canines forming the longest (mean = 1,977 ± 295 days), followed by second molars (mean = 1,176 ± 179 days) and first molars (mean = 1,094 ± 154 days). Initial cusp formation values, estimated through chronological overlap between teeth, allowed for a more accurate reconstruction of crown completion timing. Accentuated Lines prevalence peaked at 12 and 44 months, likely reflecting early childhood dietary transitions and the differential recording of stress events across different crown regions. Calculus analysis identified starch granules from cereals (Triticeae) and legumes (Fabaceae), fungal spores ( Saccharomyces ), and plant fibers, indicating diverse dietary practices, food processing, and extra-masticatory activities. This interdisciplinary approach reinforces the validity of combining histomorphometric and micro-residue analyses to reconstruct childhood health, adult diet, and lifestyle. Our findings align with previous research while emphasizing population-specific variations. This study enhances understanding of Iron Age biocultural adaptations, offering insights into developmental and dietary behaviors in this ancient Italian community.